O97 ADJUVANT CHEMORADIOTHERAPY IS BENEFICIAL IN MARGIN POSITIVE PATIENTS FOLLOWING NEO-ADJUVANT CHEMOTHERAPY AND SURGERY FOR LOWER OESOPHAGEAL AND GOJ ADENOCARCINOMA. (23rd November 2019) - Bott, R; Zylstra, J; Wilkinson, M; Knight, W; Baker, C; Kelly, M; Maisey, N; Beckmann, K; Van Hemelrijck, M; Gossage, J; Allum, W; Smyth, E; et al.
Abstract: Aim: The aim of this study was to assess the survival benefit of adjuvant therapy in margin positive patients following neo-adjuvant chemotherapy and surgery for lower oesophageal and GOJ adenocarcinoma. Background & Methods: The role of adjuvant therapy in oesophago-gastric adenocarcinoma patients treated by neo-adjuvant chemotherapy is contentious. In UK practice, surgical resection margin status is often used to stratify patients into receiving adjuvant treatment. Two prospectively collected UK institutional databases were combined. Patients were classified by the adjuvant therapy received. Crude and adjusted Cox regression analyses compared overall and recurrence free survival according to the adjuvant treatment, stratified by resection margin status. Recurrence patterns were assessed as a secondary outcome. Results: From a total of 616 patients, 242 had positive margins. In this R1 resection group, 112 patients (46%) received adjuvant chemoradiotherapy compared to 46 patients (19%) who received adjuvant chemotherapy and 84 patients (35%) who received no adjuvant treatment. On adjusted analysis, pathological N3 status (p<0.001) and poor differentiation (p=0.024) were independently associated with overall survival. When stratified by tumour response to neo-adjuvant chemotherapy, a significant survival benefit in non-responders (Mandard Grade 4&5, adjuvant chemoradiotherapy HR 0.61 95%CI 0.38-0.97; p=0.037) was observed. Additionally, adjuvant chemoradiotherapy significantly improved recurrence free survival (HR 0.59 95%CI 0.38-0.94; p=0.026) with a specific benefit for systemic recurrence (HR 0.56 95%CI 0.33-0.94; p=0.027) in both responder (Mandard Grade 1-3) and non-responder (Mandard Grade 4&5) patient groups. Conclusion: Adjuvant chemoradiotherapy improves overall survival, recurrence-free survival and systemic recurrence rates in R1 resection patients. This pattern is most pronounced in non-responders (Mandard 4&5) to neo-adjuvant chemotherapy suggesting a change in strategy to be effective for this specific patient group.